Risks: newspapers’ representation of violence against minority group in Pakistan - Abdullah Khoso, (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
Ahmadis are a religious minority group whose presence is detested by majority group in Pakistan. In 2014, in result of a mob attack, three Ahmadis had died in Pakistan. The national and international media reported the incident with different risky contexts and perspectives about attackers and people being attacked but these contexts have been given little space in academic discourse. The purpose of the article is to explore the types of risks reported, identified and located in the media text and investigate the extent to which the media crossed the legal and social boundaries of risks in representing groups. In this regard, content analysis was conducted of two widely circulated Pakistani newspapers namely The News and Dawn, and also of two western newspapers (namely Daily Mail, New York Times) which provided detailed news reporting of the incident. The article reveals that Pakistani newspapers represented Ahmadis the way as the law dictates, which shows that these did not cross legal boundaries, whereas the international newspapers represented Ahmadis against the law and considered these as a sect of Islam and a reform group within Islam, thus these crossed legal boundaries of risks. In general newspapers identified and located various risks located in Pakistani society, and these alleged social environment which was against any voice raised for legal reforms and freedom of speech. These newspaper suggested to reform the law, in doing so, these crossed dangerous social boundaries of risks. The article brings new insights about a sensitive religious-political conflict between groups which is hardly recognized in academia from cultural risk perspective but deeply enmeshed in the media text.